Diversity and Characteristics of Spaza Shops in South Africa - Willie, Michael (Manunggal Halim Jaya, 2025)
This review paper examines the diversity and characteristics of Spaza shops across various communities, emphasizing their socio-economic and cultural importance. As informal retail outlets, Spaza shops are vital in addressing economic inequality by providing affordable goods and promoting local employment and entrepreneurship. The paper analyzes the socioeconomic factors driving their establishment, influence on community interactions, and financial contribution to regional job creation. It also explores the challenges Spaza shop owners face, such as limited access to financing, regulatory barriers, and market competition, while offering recommendations for sustainable development. Additionally, the review considers ownership structures, the impact of foreign ownership, and concerns about food safety. The lack of regulatory oversight and its effects on public health and the integrity of informal retail are also discussed. This comprehensive analysis highlights the need for targeted interventions and regulatory reforms to strengthen the resilience and sustainability of Spaza shops.